2017
DOI: 10.1093/mnras/stx726
|View full text |Cite
|
Sign up to set email alerts
|

ALMA observations of cold molecular gas in AGN hosts at z ∼ 1.5 – evidence of AGN feedback?

Abstract: Similarly to the cosmic star formation history, the black hole accretion rate density of the Universe peaked at 1< z <3. This cosmic epoch is hence best suited for investigating the effects of radiative feedback from AGN. Observational efforts are underway to quantify the impact of AGN feedback, if any, on their host galaxies. Here we present a study of the molecular gas content of AGN hosts at z∼1.5 using CO[2-1] line emission observed with ALMA for a sample of 10 AGNs. We compare this with a sample of galaxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 93 publications
(155 reference statements)
8
74
0
Order By: Relevance
“…The inferred molecular masses (or upper limits) are clearly below what observed in main-sequence galaxies with similar redshift and SFR, while they are comparable to molecular masses observed in active galaxies (Figure 4). Indeed, the depletion timescale, which is the time required for the outflow to remove the gas from the galaxy (τ dep = M gas /SFR), estimated for each QSOs of our sample (τ dep < 800 Myr) is consistent to those observed in high-z submillimetre galaxies (SMGs) and obscured QSOs at z = 1.5 − 2.5 (Banerji et al, 2017;Kakkad et al, 2017).…”
Section: Molecular Gassupporting
confidence: 79%
“…The inferred molecular masses (or upper limits) are clearly below what observed in main-sequence galaxies with similar redshift and SFR, while they are comparable to molecular masses observed in active galaxies (Figure 4). Indeed, the depletion timescale, which is the time required for the outflow to remove the gas from the galaxy (τ dep = M gas /SFR), estimated for each QSOs of our sample (τ dep < 800 Myr) is consistent to those observed in high-z submillimetre galaxies (SMGs) and obscured QSOs at z = 1.5 − 2.5 (Banerji et al, 2017;Kakkad et al, 2017).…”
Section: Molecular Gassupporting
confidence: 79%
“…This scenario is supported by the observation of low gas fraction in AGN host galaxies (e.g., Brusa et al 2015;Kakkad et al 2017), as well as the AGNdriven molecular gas outflow (Cicone et al 2014;Feruglio et al 2015). In addition, it has been reported that AGN hosts preferentially lie in the green valley or below the main sequence (Nandra et al 2007;Salim et al 2007;Silverman et al 2008;Ellison et al 2016;Smith et al 2016), suggesting that AGN could drive the transition from the star-forming to the quiescent phases.…”
Section: Discussionmentioning
confidence: 70%
“…Aird et al 2010), so there is much interest in unravelling the signatures of AGN feedback on molecular gas in these distant AGN hosts (e.g. Brusa et al 2015;Kakkad et al 2017).…”
Section: Comparisons To Agn Host Galaxies At High Redshiftmentioning
confidence: 99%
“…Recently, Kakkad et al (2017) reported lower t dep and molecular gas fractions from an ALMA survey of ten X-ray selected AGN at z ∼ 1.5. In the scenario of suppressive AGN feedback on star formation, their results are interpreted as widespread evidence for the prompt removal of star-forming molecular gas, possibly by an outflow, which depresses f gas .…”
Section: Comparisons To Agn Host Galaxies At High Redshiftmentioning
confidence: 99%
See 1 more Smart Citation